Natural occurrence of Fusarium proliferatum on chestnut in Italy and its potential entomopathogenicity against the Asian chestnut gall wasp Dryocosmus kuriphilus - Tosi, L.; Beccari, G.; Rondoni, G.; Covarelli, Lorenzo; Ricci, C. (2015)
© 2014, Springer-Verlag Berlin Heidelberg. The Asian chestnut gall wasp Dryocosmus kuriphilus (DK) is one of the most important pests of chestnut trees worldwide, and sustainable control measures are urgently required for its control. In this study, the recurring mycoflora associated with DK galls in some Italian chestnut orchards was identified, and two Fusarium proliferatum strains (I3 and I4) were tested for their entomopathogenicity toward DK and their pathogenicity to chestnut in order to evaluate their potential as biocontrol agents. The two F. proliferatum strains, both isolated from the inside of DK galls and often covering dead bodies of larvae, pupae, and adults, caused a natural insect infection of about 4 % and resulted to be non-pathogenic to chestnut plants, while they induced 33 and 97 % of larvae mortality when applied in laboratory experiments to intact DK fresh or sectioned galls, respectively. Both strains infected maize seedlings, used as non-target hosts, and produced fumonisins in vitro. The efficacy in controlling DK in the galls, the absence of pathogenicity to chestnut, and the lower mycotoxin production indicated strain I3 as a promising biocontrol agent of the considered pest.